2016
DOI: 10.1051/0004-6361/201628670
|View full text |Cite
|
Sign up to set email alerts
|

The warm absorber in the radio-loud quasar 4C +74.26

Abstract: Outflows of photoionized gas are commonly detected in the X-ray spectra of Seyfert 1 galaxies. However, the evidence for this phenomenon in broad line radio galaxies, which are analogous to Seyfert 1 galaxies in the radio-loud regime, has so far been scarce. Here, we present the analysis of the X-ray absorption in the radio-loud quasar 4C +74.26. With the aim of characterizing the kinetic and the ionization conditions of the absorbing material, we fitted jointly the XMM-Newton Reflection Grating Spectrometer (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The spectral emission components are attenuated by Galactic absorption, excess neutral absorption above the Galactic value, and a warm absorber (Ballantyne 2005;Di Gesu & Costantini 2016). Tombesi et al (2014) also detected signs of a highly ionized ultra-fast outflow in the XMM-Newton data of the source.…”
mentioning
confidence: 87%
“…The spectral emission components are attenuated by Galactic absorption, excess neutral absorption above the Galactic value, and a warm absorber (Ballantyne 2005;Di Gesu & Costantini 2016). Tombesi et al (2014) also detected signs of a highly ionized ultra-fast outflow in the XMM-Newton data of the source.…”
mentioning
confidence: 87%
“…An in-depth analysis of the rich X-ray dataset for 4C +74.26, using the most recent observations with XMM-Newton, Chandra, and NuSTAR, has been reported by Di Gesu & Costantini (2016) and Lohfink et al (2017). Here we re-analyze the NuSTAR data for the target in the hard X-ray regime, focusing predominantly on the characterization of the main parameters of the underlying accretion disk, in particular its inner radius, in the context of the multi-wavelength correlation studies reported in the previous Section 3.2.…”
Section: X-ray Spectral Analysismentioning
confidence: 99%
“…In addition, in order to account for the presence of a warm absorber in the source (e.g. Di Gesu & Costantini 2016), as well as the Galactic absorption, we combined RELXILL with the TBABS (Wilms et al 2000) and WARMABS models.…”
Section: X-ray Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The intrinsic cold absorption is low and poorly constrained, and is fixed at N H = 0.19 × 10 22 cm −2 which is the averaged best-fit value from four observations. A warm absorber (with parameters fixed at the values derived by Di Gesu & Costantini 2016) are included. For relxill, we fix a = 0 , r in = 6 R g , r out = 400 R g , and we leave emissivity profile index, ξ and the iron abundance A F e free to vary, and the cosine Figure 11.…”
Section: The Usefulness Of Spectra Ratiosmentioning
confidence: 99%